Two new species of Blaberidae (Blattaria) collected in the Santa Lúcia Station, Espírito Santo State, Brazil - Lopes, Sonia Maria; de Oliveira, Edivar Heeren; Assumpção, Mariana (Zootaxa, 2014)
This contribution presents two new species belonging to the genera Audreia (Shelford, 1910) and Epilampra Burmeister, 1838, subfamily Epilamprinae (Blattaria, Blaberidae). The Blaberidae include large and medium-bodied species with a high adaptive capacity. The new taxa were collected in Espírito Santo State and evaluated based on the analysis of subgenital and supranal plates and genital parts, by means of standard dissection techniques, by comparison with specimens of the corresponding genera deposited in the collection of the Museu Nacional and with published descriptions.